JUAL BELI MELALUI JEJARING SOSIAL BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 PERUBAHAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI TRANSAKSI ELEKTRONIK - Mestiana Wati dan Yunimar (Fakultas Hukum Universitas Tamansiswa Padang, 2019)
Buying and selling through social media is currently growing very rapidly along with the development of technologies such as Facebook, line, Instagram, and others. Buying and selling online can be done anywhere and anytime without wasting time to go out of the house, this is what causes many interested in buying and selling online. Buying and selling through social networking is regulated in the Civil Code IIII book and the regulation of Electronic Information Transactions Law No. 19 of 2016 concerning Amendment to Law No. 11 of 2008 concerning Electronic Transaction Information. Based on the results of the research, buying and selling through social networks can be carried out anywhere and anytime, by using social media applications such as Facebook, Instagram, line, and others. In carrying out this sale and purchase agreement, obstacles encountered include, among other things, the inaccuracy in delivery time, the incompatibility of the items ordered. Based on this the authors would like to further conduct research with the formulation of the problem, How is the sale and purchase of social networks based on Law No. 19 of 2016 Amendment of Law No. 11 of 2008 concerning Electronic Transaction Information, and are there any problems that arise from the conduct of buying and selling through social networks and what is the solution. This problem is resolved by way of delays in the delivery of goods and it will be confirmed to consumers, goods that are defective or not in accordance with the order will be immediately replaced with a delivery time of 3 days and there are also businesses that do not accept the exchange of goods. Delayed shipping costs will also be delayed buyer orders. The suggestion is that both businesses and consumers must be honest in providing information data.